The effect of sitting position changes from pedaling rehabilitation on muscle activity. Issue 3 (17th February 2021) - Zongxing, Lu; Xiangwen, Wei; Shengxian, You
Abstract: Sports injuries or traffic accidents make the individuals bedridden for a long duration, easily causing the disuse of lower limb muscles. Exercise rehabilitation is an effective method to improve muscle activity; however, currently, exercise therapy mainly relies on the experience of rehabilitation physicians for determining the rehabilitation parameters. In this paper, we establish a human–machine coupling system model for disuse atrophy of lower limb muscles. We analyze the influence of sitting position on pedaling rehabilitation. The relationship between the sitting position and muscle effect of lower limb muscle is calculated. We optimized the parameters to analyze muscle force and activity distribution in the muscle group during different sitting positions, and the rehabilitation risk area and the invalid area were identified from the distribution map, which helps quantify the maximal exercise of muscles without causing secondary muscle damage. The mapping relationship between sitting position and muscle force was established in this study. Further, muscle activity mapping is performed for overall assessment. Muscle activity assessment considered the training intensity of small muscles and avoids secondary injury of small muscle. The corresponding designated sitting posture improved the intensity of muscle training and shortened the rehabilitation cycle. Systematic distribution areas for different rehabilitation effects in pedal exercises are presented and provide the sitting position distribution areas for patients in the early, middle, and late stages. The proposed model provides theoretical guidance for rehabilitation physicians.